An Approach to Data Transmission Process Modelling in Automated Power Accounting Systems. Issue 1 (February 2021) - Lyubchenko, A A; Kopytov, E Y; Malyutin, A G; Bogdanov, A A
Abstract: An accurate accounting of electricity consumption is a relevant task for the improvement of energy efficiency both in industry and in housing and communal services. An important step in solving this task is the deployment of automated metering systems that allow obtaining analytical information required for development and adjustment of energy saving programs. The development of data transmission technologies over cellular networks has led to the widespread use of wireless channels for information exchange in automated energy control and monitoring systems. As both main and reserve communication channels, these systems can use technologies with channel switching (GSM CSD) and packet switching (GPRS). The choice of a particular data transmission technology in this case depends on a number of technical or economic factors. The aim of this work is the development of a conceptual model of the data transmission process in the automated energy consumption monitoring systems with direct connection of meters via GSM CSD and GPRS channels. For modeling the physical layer of the radio channel the model of signal propagation of Okamura-Hata was chosen. Calculation of call blocking probability is based on Erlang-B model. MIR C-01 and CET-4TM have been chosen as electric energy meters. In the work, the conceptual model of data transmission process in the monitoring system with GSM CSD and GPRS channels is offered, being a basis for its further mathematical formalization for the purpose of modelling of an information exchange between elements of the automated energy consumption monitoring system.